FACTORS INFLUENCING THE START OF BUSINESS FOR TRANSGENDER ENTREPRENEURS IN TAMIL NADU WITH SPECIAL REFERENCE TO SELECTED DISTRICTS (International Journal of Food and Nutritional Sciences, 2022)
Transgender entrepreneurs are making significant contributions to the world for business and entrepreneurship. They bring unique perspectives and experiences to the table, which can help them identify untapped markets and create innovative solutions that cater to diverse communities. There are just a few example of transgender entrepreneurs who are making a difference in their respective in their respective fields. As society becomes more inclusive and accepting of diverse identities, it’s likely that we’ll see more Transgenders individuals starting business and creating innovative solutions to address the needs of underserved communities Transgender people are becoming entrepreneurs and engaging in business, knowing that there will be some problems and many hardships before and after starting the business. But we are always encouraging and motivating each other. Also, the community, relatives, friends, and family are encouraging many people to become entrepreneurs. The study was conducted to find out who motivates transgender entrepreneurs the most.